Coelomic Fluid Evaluation in Pisaster ochraceus Affected by Sea Star Wasting Syndrome: Evidence of Osmodysregulation, Calcium Homeostasis Derangement, and Coelomocyte Responses - Wahltinez, Sarah J.; Newton, Alisa L.; Harms, Craig A.; Lahner, Lesanna L.; Stacy, Nicole I. (Frontiers in Veterinary Science, 2020)
Sea Star Wasting Syndrome (SSWS) is one of the largest marine wildlife die-offs ever recorded, killing millions of sea stars from more than 20 Asteroid species from Alaska to Mexico from 2013 to 2015 from yet undetermined cause(s). Coelomic fluid surrounds the sea star’s organs, playing critical roles in numerous systemic processes, including nutrient transportation and immune functions. Coelomocytes, which are cellular components of coelomic fluid and considered functionally equivalent to vertebrate leukocytes, are responsible for innate cell-mediated immunity. The objectives of this study were to (1) evaluate changes in coelomic fluid chemistry, coelomocyte counts, and cytology from ochre sea stars (Pisaster ochraceus) (n=55) with clinical signs consistent with SSWS at varying intensity (SSWS score 1: n=4, score 2: n=2, score 3: n=3, score 4: n=18, score 5: n=26) in comparison to coelomic fluid from clinically normal sea stars (n=26) and to (2) correlate SSWS score with cellular and biochemical analytes. SSWS-affected sea stars had wider ranges of all electrolytes, except calcium; statistically significantly higher chloride, osmolality, and total protein; lower calcium; and higher coelomocyte counts when compared to clinically normal sea stars maintained under identical environmental conditions. Free and/or phagocytized bacteria were noted in 29% (16 of 55) coelomic fluid samples from SSWS-affected sea stars but were absent in clinically normal sea stars. SSWS score correlated significantly with increasing chloride concentration, osmolality, and coelomocyte counts. These chemistry and cytological findings in coelomic fluid of SSWS-affected sea stars provide insight into the pathophysiology of SSWS as these results suggest osmo- and calcium dysregulation, coelomocyte responses, and presumptive opportunistic bacterial infection in SSWS-affected sea stars. This information provides potential future research applications for the development of treatment strategies for sea stars in managed care and for understanding the complexity of various biochemical and cellular pathophysiological mechanisms involved in sea star wasting.